Regenerative Treatments to Enhance Orthopedic Surgical Outcome. Issue 4 (10th April 2015) - Murrell, William D.; Anz, Adam W.; Badsha, Humeira; Bennett, William F.; Boykin, Robert E.; Caplan, Arnold I.
Abstract: In orthopedic surgery there has been a never‐ending quest to improve surgical outcome and the patient's experience. Progression has been marked by the refinement of surgical techniques and instruments and later by enhanced diagnostic imaging capability, specifically magnetic resonance. Over time implant optimization was achieved, along with the development of innovative minimally invasive arthroscopic technical skills to leverage new versions of classic procedures and implants to improve short‐term patient morbidity and initial, mid‐term, and long‐term patient outcomes. The use of regenerative and/or biological adjuncts to aid the healing process has followed in the drive for continual improvement, and major breakthroughs in basic science have significantly unraveled the mechanisms of key healing and regenerative pathways. A wide spectrum of primary and complementary regenerative treatments is becoming increasingly available, including blood‐derived preparations, growth factors, bone marrow preparations, and stem cells. This is a new era in the application of biologically active material, and it is transforming clinical practice by providing effective supportive treatments either at the time of the index procedure or during the postoperative period. Regenerative treatments are currently in active use to enhance many areas of orthopedic surgery in an attempt to improve success and outcome. In this review we provide a comprehensive overview of the peer‐reviewed evidence‐based literature, highlighting the clinical outcomes in humans both with preclinical data and human clinical trials involving regenerative preparations within the areas of rotator cuff, meniscus, ligament, and articular cartilage surgical repair.